Teledentistry: A Concept in Need of Clarification. A Literature Review - Tasayco-Torbisco, Gaby L. (2023)
Teledentistry has experienced rapid adoption, revealing a lack of consensus in its definition and usage. Existing definitions provide insight into its applications but lack clarity regarding teledentistry’s conceptual framework, which limits its implementation in professional practice. Therefore, a literature search was conducted using the PubMed database and the Google web search engine to compile the available teledentistry definitions. In total, 63 definitions were found, encompassing e-health, telehealth, and telemedicine. Although most of them included teledentistry as part of telemedicine, the scopes expressed in their definitions reflect that teledentistry goes beyond patient care. Hence, it is necessary to delineate concepts and differentiate between e-health domains for a better understanding of the term.